Efficient conversion of anti-phase spin order of protons into 15N magnetisation using SLIC-SABRE. (2nd October 2019) - Knecht, Stephan; Kiryutin, Alexey S.; Yurkovskaya, Alexandra V.; Ivanov, Konstantin L.
ABSTRACT: SABRE (Signal Amplification By Reversible Exchange) is a technique for enhancement of NMR (Nuclear Magnetic Resonance) signals, which utilises parahydrogen ( p H2, the H2 molecule in its nuclear singlet spin state) as a source of non-thermal spin order. In SABRE experiments, p H2 binds transiently to an organometallic complex with a to-be-polarised substrate; subsequently, spin order transfer takes place and the substrate acquires non-thermal spin polarisation resulting in strong NMR signal enhancement. In this work, we argue that the spin order of H2 in SABRE experiments performed at high magnetic fields is not necessarily the singlet order but rather anti-phase polarisation, S 1 z S 2 z . Although SABRE exploits p H2, i.e. the starting spin order of H2 is supposed to be the singlet order, in solution, S− T 0 conversion becomes efficient once p H2 binds to a complex. Such a variation of the spin order, which becomes S 1 z S 2 z, has an important consequence: NMR methods used for transferring SABRE polarisation need to be modified. Here we demonstrate that methods proposed for the initial singlet order may not work for the S 1 z S 2 z order; however, a simple modification makes them efficient again. GRAPHICAL ABSTRACT: